Editor's Choice – Network Meta-Analysis of Carotid Endarterectomy Closure Techniques. (February 2021) - Lazarides, Miltos K.; Christaina, Eleni; Argyriou, Christos; Georgakarakos, Efstratios; Tripsianis, Gregory; Georgiadis, George S.
Abstract : Objective: There is discordance between reviews comparing eversion endarterectomy (EvE) with conventional carotid endarterectomy (CEA) mostly because under this term various "closure" techniques are included, from direct closure to a wide spectrum of patches with different materials. Data sources: MEDLINE (via PubMed) and SCOPUS. Review methods: This was a systematic review of the Medline (via PubMed) and SCOPUS databases for randomised controlled trials (RCTs) comparing different CEA closure techniques. Network meta-analysis (NMA) was performed with a frequentist approach. The primary and the secondary outcome measures were the 30 day combined stroke and death rate and the late restenosis rate, respectively. Results: Twenty-three RCTs were finally included in the NMA with a total of 4440 patients randomised, representing seven different techniques (primary carotid closure, n  = 753; EvE, n  = 431; vein patch closure, n  = 973; polytetrafluoroethylene [PTFE] patch, n  = 948; Dacron patch, n  = 828; bovine pericardium patch, n  = 249; and polyurethane patch, n  = 258). NMA showed that EvE had a decreased 30 day combined stroke and death rate vs. all other methods of arterial closure, with the exception of PTFE and bovine pericardium patching. Additionally, EvE was associated with the lowest restenosis rate vs. all other methods of arterial closure after CEA. EvE was significantly superior to Dacron patches with regard to late restenosis, with the prediction intervals (PIs) lying completely on the beneficial side (risk ratio 0.06; PI 0.01–0.58) and increasing confidence of this comparison. Rare catastrophic complications of vein patch blow out or synthetic patch infection were reported in 0.2% of the total ( n  = 9/4 400) and no comparisons were made. Conclusion: EvE and patching with bovine pericardium or PTFE is associated with a lower incidence in both short term and late undesired outcomes following CEA and seems to represent the best choice compared with other carotid closure techniques. These results may support the vascular surgeon's choice of technique/patch material.